Brain Structural and Functional Changes in Cognitive Impairment Due to Alzheimer’s Disease - Ávila-Villanueva, Marina; Marcos Dolado, Alberto; Gómez-Ramírez, Jaime; Fernández-Blázquez, Miguel (Frontiers in Psychology, 2022)
Cognitive neuropsychology looks for an alignment between structural a functional brain features to explain physiological or pathological processes. Several brain structural and functional changes occurring during disease are found at the end of the patient´s life, but we need to know more about what happens before its onset. For that, we need earlier markers to prevent the cognitive impairment. In this short work, we have tried to start describing the structural and functional changes found in disease, and those previous features taking place before clinical diagnosis.